Keabsahan Persetujuan Elektronik dalam Pembentukan Perikatan Digital - M. Jihan Febriza; Burhanudin; Al Pyan Syah Marszedi (RETORIKA: Journal of Law, Social, and Humanities, 2026)
This study aims to analyze the validity of electronic consent in the formation of digital obligations under Indonesian law and to formulate a legal framework for obligations that ensures legal certainty regarding its use in digital transactions. The research employs a normative legal research method, utilizing both statutory and conceptual approaches. Legal materialscomprising primary, secondary, and tertiary sources were gathered through literature review and subsequently analyzed using legal interpretation, legal theory, and legal principles. The findings indicate that electronic consent constitutes a valid expression of intent, provided it meets the requirements for a valid agreement, is given freely without defects of will, and is supported by an electronic system that is reliable, secure, and accountable. Ensuring legal certainty regarding its use requires a legal framework for obligations that integrates established principles of contract law with the unique characteristics of digital transactions through the harmonization of norms and the strengthening of electronic evidentiary mechanisms; such a framework would provide legal protection, ensure a balance of positions between the parties, foster trust in digital transactions, and reinforce legal certainty in the conduct of electronic commerce in Indonesia